2022
DOI: 10.3390/molecules27051724
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure, Topology, DFT and Hirshfeld Surface Analysis of a Novel Charge Transfer Complex (L3) of Anthraquinone and 4-{[(anthracen-9-yl)meth-yl] amino}-benzoic Acid (L2) Exhibiting Photocatalytic Properties: An Experimental and Theoretical Approach

Abstract: Here, we report a facile route to the synthesizing of a new donor–acceptor complex, L3, using 4-{[(anthracen-9-yl)meth­yl] amino}­benzoic acid, L2, as donor moiety with anthraquinone as an acceptor moiety. The formation of donor–acceptor complex L3 was facilitated via H-bonding and characterized by single-crystal X-ray diffraction. The X-ray diffraction results confirmed the synthesized donor–acceptor complex L3 crystal belongs to the triclinic system possessing the P-1 space group. The complex L3 was also cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Based on the optimized structure and HOMO–LUMO, some molecular parameters related to chemical reactivity (SCF minimum energies, polarizability, thermodynamic parameters, dipole moments) for the complexes are presented in Table 4 in the gas phase. 61,80…”
Section: Resultsmentioning
confidence: 99%
“…Based on the optimized structure and HOMO–LUMO, some molecular parameters related to chemical reactivity (SCF minimum energies, polarizability, thermodynamic parameters, dipole moments) for the complexes are presented in Table 4 in the gas phase. 61,80…”
Section: Resultsmentioning
confidence: 99%
“…The red color in the map signifies an electronegative region with minimum electrostatic potential that divulges its susceptibility to electrophilic attack. Similarly, the blue color represents an electropositive region liable for the nucleophilic attack, whereas green is a region of zero potential. , The MEP diagrams revealed that the red region corresponds to the oxygen atom of the carbonyl group of dimedone, imine group of the imidazole ring, and oxygen atoms of substituted nitro, hydroxyl, and methoxy groups of the acetophenone ring, which indicates its most reactivity toward the intermolecular hydrogen-bonding interactions. The hydrogen atoms of the hydroxyl group of the dimedone ring exhibit the electropositive nature as represented in blue regions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These high values could be ascribed to the high donating ability of TIGC, prominent electron affinity of TCNQ, and the high electric permittivity of ACN. Moreover, these high values demonstrate the dissociation of the outer sphere CTC (TIGC-TCNQ) resulting in the formation of radical ions of the two species with high electrostatic attraction, as shown in Scheme 3 [ 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%